Pick any term to divide it by the previous term. I'm going to pick the second term and divide it by the first term.
r = common ratio r = (term 2) divided by (term 1) r = (4/9) divided by (-4/3) r = (4/9) * (-3/4) r = (4*(-3))/(9*4) r = -12/36 r = -1/3 The common ratio is -1/3
This means you multiply each term by -1/3 to get the next term
For instance term 2 = r*(term 1) term 2 = (-1/3)*(-4/3) term 2 = ((-1)*(-4))/(3*3) term 2 = 4/9
1- false a positive is greater than a negative so clearly there could be positive answers to the inequality. 2-true since the numbers and sign flipped it would still be the same